Pemanfaatan Media Sosial sebagai Media Dakwah Islam dalam Kemajuan Perkembangan Teknologi - Hisny Fajrussalam; Intan Dwiyanti; Nisrina Fairuz Salsabila; Rinanda Aprillionita; Siti Auliakhasanah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
In this era of increasing globalization, many people use various social media platforms such as Facebook, Instagram, Twitter, Telegram, WhatsApp, etc. Many people use social media platforms that aim to achieve their desires such as social, economic and religious.Social media also has a big impact on anyone who use it positively, such as preachers who always provide many benefits to Muslim brothers and sisters in spreading da’wah. With social media, da’wah can be heard anytime and anywhere. The purpose of preaching is to always remind all that life in this world is only temporary and the hereafter is an eternal place, and the most powerful is only Allah SWT. This study aims to find out about the use of social media as a medium for Islamic da’wah in the advancement of technological development. In this study, a survey was conducted on 52 respondents from among lecturers/teachers, students, and the general public. The result obtained from the research are a discussion of knowing and understanding the use and role of social media as a medium of da’wah and the challenges, opportunities and threats of preaching in social media.